Geoinformation mapping algorithm of Chernivtsi region land resources on the basis of spatial data infrastructures - Бондаренко, Едуард Леонідович; Смірнов, Я. (Київський національний університет імені Тараса Шевченка, 2015)
In the article is formulated geoinformation mapping algorithm of land resources mapping on the basis of spatial data infrastructures (SDI). Defined major and minor elements of SDI needed for geoinformation mapping of land resources and the basic requirements to the sources and forms of their presentation. As a result of analysis of the SDI components, created model of their interaction and visualization provided in the forms of series of static and interactive maps.

В статті сформульовано алгоритм геоінформаційного картографування (ГК) земельних ресурсів на основі інфраструктур просторових даних (ІПД). Визначені головні та другорядні елементи ІПД, необхідні для ГК земельних ресурсів, встановлені основні вимоги до їх джерел та форм представлення. В результаті аналізу кожної зі складових ІПД побудовано модель їх взаємодії та шляхів представлення у вигляді серій статичних та інтерактивних карт.
Алгоритм геоінформаційного картографування земельних ресурсів Чернівецької області на основі інфраструктур просторових даних
Berljant A., Vostokova A., Kravcova V. (eds.) Kartovedenie: Uchebnik dlja vuzov [Cartography: Textbook for high schools], Moscow: Aspekt Press, 2003, 477 p. [in Russian] Bondarenko E. L. Invariantni skladovi infrastruktur prostorovykh danykh dlia riznykh terytorialnykh rivniv heoinformatsiinoho kartohrafuvannia [Invariant components of spatial data infrastructures for different territorial levels geo-mapping], Problemy bezperervnoi heohrafichnoi osvity i kartohrafii : Zbirnyk naukovykh prats, 2010, Issue 11, pp. 30–36 [in Ukrainian] Karpinskyi Yu. O. Pro formuvannia Natsionalnoi infrastruktury heoprostorovykh danykh v Ukraini [On the formation of the National geospatial data infrastructure in Ukraine], Heohrafiia v informatsiinomu suspilstvi: zb. nauk. prats u 4-kh t., Kyiv: VHL Obrii, 2008, 1, pp. 72–80 [in Ukrainian] Proekt Zakonu Ukrainy “Pro natsionalnu infrastrukturu heoprostorovykh danykh” vid 03.12.2009 roku [Draft Law of Ukraine “On the national geospatial data infrastructure” of 03.12.2009] Available at: http://w1.c1.rada.gov.ua/pls/zweb2/webproc4_2?id=&pf3516=5407&skl=7 [in Ukrainian] Smirnov Ya. Suchasnyi stan i perspektyvni napriamy kartohrafuvannia zemelnykh resursiv na osnovi danykh dystantsiinoho zonduvannia Zemli [Current status and future directions of mapping land resources based on remote sensing data], Naukovyi visnyk Volynskoho universytetu im. L. Ukrainky : Heohrafichni nauky, Lutsk : RVV “Vezha”, Seriia: heohrafiia, 2012, 9, pp. 52–57 [in Ukrainian] Smirnov Ya. Naukovo-metodychni osnovy heoinformatsiinoho kartohrafuvannia zemelnykh resursiv Chernivetskoi oblasti [Scientific and methodical bases geo-mapping of land resources Chernivtsi region], Candidate Thesis, Kyiv, 2015, 20 p. [in Ukrainian] Dyshlyk O., Karpinskyi Yu., Kucher O., Sossa R. (eds.) Stan ta osnovni napriamky rozvytku topohrafo-heodezychnoi i kartohrafichnoi diialnosti v Ukraini [State and the main directions of topographic and geodesic mapping activities in Ukraine], Kyiv: NDIHK, 2006, 76 p. [in Ukrainian] Chernivetska oblast. Polityko-administratyvna karta, masshtab 1:250 000 [Chernivtsi region. Political and administrative map, scale 1: 250 000], Available at: http://ukrmap.com.ua/catalog/skladani-karti/oblastej-ta-regioniv-ukrajini/chernivetska-oblast-politiko-administrativna-karta-m-b-1250-000/?id=143 [i Ukrainian] CORINE Land Cover Legend Available at : http://sia.eionet.europa.eu/CLC2006/CLC_Legeng.pdf [in English] About the European Nature Information System, EUNIS, Available at: http://eunis.eea.europa.eu/about [in English] INSPIRE DIRECTIVE, Available at: http://inspire.jrc.ec.europa.eu [in English] Masser I. GIS Worlds: Creating Spatial Data Infrastructures / Ian Masser, ESRI Press: 2005, 336 p. Steiniger S. Free and open source GIS software for building a spatial data infrastructure / S. Steiniger, A. Hunter // Proceedings of the first Open Source Geospatial Research Symposium, LNG&C, Springer, Heidelberg, 2009, pp. 247–261.
Keywords: інфраструктури просторових даних; геоінформаційне картографування; земельні ресурси; земельний покрив; землекористування; spatial data infrastructure; geoinformation mapping; land resources; land cover; land use